Some contemporary Protestant theological reflections on pluralism: implications for Christian-Muslim understanding - Smith, Jane I. (Islam and Christian-Muslim relations, 1997)
Theological writings about the relationship of Christianity to other religions are often cast into one of three general categories: exclusivist, inclusivist and pluralist. This essay reviews six twentieth‐century Protestant Christian theologians and academics who have reflected on ways in which Christians can understand their faith in the light of the religion of Islam. Some have spent their lives relating to Muslims and deal specifically with its implications for Christian understanding, while others treat Islam more generally as part of the larger issue of Christianity in the light of contemporary religious pluralism. As a whole they are representative of the range of theological responses suggested in the above categories.